Modeling Bacterial Adhesion to Unconditioned Abiotic Surfaces - Spengler, Christian; Maikranz, Erik; Santen, Ludger; Jacobs, Karin (Frontiers in Mechanical Engineering, 2021)
Understanding bacterial adhesion as a first step towards biofilm formation is of fundamental interests in many applications. While adhesion to abiotic surfaces is directly relevant for some applications it also provides a controlled reference setting to study details of the adhesion process in general. This review describes the traditional approaches from contact mechanics and (x)DLVO, which treat the bacterium-substratum interaction in a continuous manner. We will discuss its shortcomings and provide an introduction to more recent approaches, which understand the adhesion process as a result of individual stochastic interactions of many macromolecules with the substratum.